2015
DOI: 10.1016/j.jvs.2015.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of intraoperative vascular surgery consultations

Abstract: Unexpected intraoperative need for vascular surgical expertise occurs often enough that vascular surgeons should be regarded as an essential operating room resource to the general operating room, nonvascular surgeons, and their patients. Intraoperative vascular surgical consultation in support of other surgeons requires a high level of open technical operative skills and is time and labor intensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 8 publications
3
44
1
Order By: Relevance
“…It has been previously documented that vascular surgeons perform relevant techniques in emergencies to control hemorrhage. In addition, their expertise in dissections around major arteries and veins and in reconstructions of major vessels can improve the likelihood of success of R0 resection in cancer surgery, using such vascular reconstruction techniques [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been previously documented that vascular surgeons perform relevant techniques in emergencies to control hemorrhage. In addition, their expertise in dissections around major arteries and veins and in reconstructions of major vessels can improve the likelihood of success of R0 resection in cancer surgery, using such vascular reconstruction techniques [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study provides quantitative data vascular surgical involvement in non-vascular surgeries. Previous studies have not reported the incidence of vascular injury that required treatment during non-vascular surgeries [ 1 ]. However, in this study, the incidence of intraoperative vascular consultation was estimated to be approximately 0.3%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations